Poorly Differentiated Thyroid Carcinoma: A Case Report - Mahendra Dewi, I Gusti Ayu Sri; Sastra, I Made Wirya; Saputra, Herman; Ekawati, Ni Putu (Gaceta Médica de Caracas, 2022)
Poorly differentiated thyroid carcinoma (PDTC) is a follicular cells neoplasm that shows limited follicular cell differentiation which is morphologically and behaviorally intermediate between differentiated carcinoma (follicular or papillary) and anaplastic carcinoma. Poorly differentiated thyroid carcinoma is rarely ranging from 0.3% to 6.7% of all thyroid cancers. These tumors are aggressive and often lethal and have a rapid and fatal outcome despite appropriate treatment.